Analysis of Commercial Enteral Formula (CEF) and Hospital Enteral Formula (HEF) usage on cost budget and patient food acceptance - Putri, Tri Putri; Mitra, Mitra; Devi, Liza Srikusuma (Majalah Kesehatan Indonesia, 2025)
The high cost of commercial enteral formulas (CEF) and the need for hospital budget efficiency, especially for patients funded by BPJS, are major concerns in nutritional services. Additionally, patient acceptance of enteral formulas is an important indicator of the success of hospital nutrition services. Therefore, hospital enteral formulas (HEF) are designed to meet patients' nutritional needs at a more affordable cost without compromising quality. The aim of this study is to analyze cost efficiency and patient acceptance of food intake when using CEF compared to HEF, as well as to develop recommendations for a more effective and efficient enteral food procurement strategy at RSUD Muhammad Sani Karimun. This study employs a qualitative approach with a case study design. The study informants include key informants, namely six patients on an enteral formula diet and nutrition kitchen staff (Pranata Jamuan), as well as supporting informants, namely the Head of Non-Medical Support Services at RSUD Muhammad Sani. Informants were selected using purposive sampling. Primary data were obtained through observations and interviews, while secondary data were collected through document analysis. The problem identification process used the fishbone method. The study results indicate that HEF is 51.64% - 52.64% more cost-efficient than CEF. Patient acceptance of HEF is relatively high, particularly in terms of taste and texture, while factors such as hygiene and lower costs are the main advantages of HEF. HEF is a more efficient alternative that still meets patients' nutritional needs. The use of HEF is recommended to optimize hospital budgets without compromising the quality of patients’ nutritional intake.